The Quest for Time - An examination of the changing dynamics of managerial attributes in the English Premier League - Desai, Malay (2009)
The aims and objectives of the study have been to examine the managerial human capital in the current football climate and understand if it has evolved. In conjunction with a changing dynamic environment, there has been a changing trend of human capital managerial attributes that allow for management stability in the English Premier League. This paper has examined the Premier league manager using different statistical techniques to understand the determinants of managerial attributes and their survivability in a world that is dominated by high financial resources (Szymanski & Smith, 1997) and expectations. The results have suggested that the football environment has evolved. By acquiring industry experience and having previous association with the club could be useful in maintaining stability. The paper also includes a critical analysis of the findings and implications for business, and finally concludes with directions for future research.